Admission to the United Nations : Charter Article 4 and the rise of universal organization - Grant, Thomas D., 1969- (Legal aspects of international organization, 2009)
Presents an account of admission to the UN, from the 1950s 'logjam' through controversies like Kosovo and Taiwan. With reference to Charter law, this book considers how Article 4 came to accommodate universality and what the future of a universal organization in a world of politically diverse States might be.